Industrial hemp: A comprehensive analysis from hemp seeds to a sustainable alternative raw material for textiles and industrial applications - Kırbaş Hatice; Battal Özgenur; Demir Saliha; Yatgın Utku; Başlar Atilla; Uzun Muhammet (Tekstilna industrija)
Hemp (Cannabis sativa L.) has historically played a significant role in textile and industrial applications. However, its production declined due to regulatory constraints and competition from other fibers. In recent years, hemp has re-emerged as a sustainable alternative due to its rapid growth, minimal water and chemical requirements, and exceptional durability. This study provides a comprehensive analysis of hemp cultivation, fiber properties, and its expanding role in industries such as textiles, construction, and biocomposites. Additionally, a life cycle assessment (LCA) is conducted to evaluate hemp's environmental impact in comparison to conventional materials like cotton and synthetic fibers. The findings highlight hemp's potential to promote sustainable production practices and reduce the ecological footprint of various industries.